Exploring the Integration of Science, Technology, Engineering, Arts, and Mathematics (STEAM) in Elementary Education: A Systematic Literature Review - Falasifah, Farah (International Conference on Elementary Education, 2025)
STEAM education in elementary schools has gained increasing global attention, driven by the need to develop 21st-century skills and integrate innovative technologies. This study employs a systematic review approach by collecting and analyzing 800 recent studies from international databases such as Scopus, Web of Science, and ERIC, published within the last five years. The primary findings reveal a significant upward trend in the use of digital and innovative media, such as augmented reality (AR), virtual reality (VR), and artificial intelligence (AI), which positively impact student motivation, critical thinking skills, and academic outcomes. However, challenges remain, including disparities in technological access, teacher preparedness, and cultural diversity across different contexts. These findings emphasize the importance of policy development that supports pedagogical innovation and enhances technological infrastructure to ensure the effective and inclusive implementation of STEAM. The study also identifies research gaps concerning long-term impacts and sustainability of STEAM programs across regions, highlighting the need for further investigation. The insights offered by this review provide strategic directions for fostering innovative, adaptive, and equitable STEAM education at both global and local levels.